Influências da educação e de doenças neurodegenerativas sobre as relações entre a memória episódica e seus correlatos neurais - Elisa de Paula França Resende (2019)
Introduction: How extrinsic and intrinsic factors of the individual interfere in the relationship between the neural substrates of episodic memory and performance in specific tests is a matter under debate in the scientific literature. Education, an example of an extrinsic factor, seems to promote the brain's greater ability to adapt to injury and prevent cognitive decline, possibly by modifying the relationship between brain structures and their functions. Neurodegenerative diseases, such as Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are examples of intrinsic factors. While in AD there is a classic deficit of episodic memory due to hippocampal involvement, in bvFTD episodic memory may also be affected, but the neural correlates of this impairment are controversial. To explore these factors, we conducted two studies: one analyzing the role of education and the other analyzing the role of neurodegenerative diseases (AD and bvFTD) in the relationship between episodic memory and its neural correlates. Study 1 - Objectives: To identify how years of education would influence the relationship between hippocampal volume and episodic memory performance. Population: One hundred and eighty-three older adults (112 cognitively healthy, 26 with cognitive impairment non-dementia and 45 with dementia), 40.1% men, median age 78, [interquartile range (IQI): 76, 82] and median education of four [IIQ: 2,10] years. Methods: Hippocampal volume was measured by structural MRI and episodic memory was assessed by the Brief Cognitive Battery (BCB) delayed score. Using multiple linear regression models, we calculated the role of educational level x hippocampal volume interaction in memory performance (outcome). Result: The higher the educational level, the stronger the relationship between left hippocampal volume and episodic memory, after adjusting for age, cognitive diagnosis, gender, the BCB learning phase, the volume of other important brain regions for episodic memory processing and the presence / intensity of white matter lesions. Study 2 - Objectives: To compare the neural correlates of episodic memory between patients with AD and bvFTD and, within the bvFTD group, to compare those with amnestic profile (n = 8) with non- amnestic profile (n = 11). Population: Sixty-one older adults (19 with bvFTD, 21 with AD and 21 cognitively healthy), 50.8% men, median age of 67 [IIQ: 59,74] years and median education of 11 [IIQ: 11,16 years. Methods: We calculated the correlations between episodic memory performance assessed by the BCB delayed recall and gray matter volumes assessed by MRI in AD and bvFTD patients. Next, we contrasted the gray matter volumes of amnestic versus non-amnestic bvFTD patients. Results: Episodic memory performance in AD patients was inversely associated with atrophy in bilateral hippocampi and left precuneus and posterior cingulate gyrus. In patients with bvFTD, there was an inverse association with hippocampi volumes bilaterally. Episodic memory did not correlate with executive functioning in any group, suggesting that memory impairment was not associated with executive dysfunction. Finally, we found that amnestic bvFTD patients had greater atrophy of the left fusiform and parahypocampal gyrus and right cingulate and precuneus regions than non-amnestic ones. Compared with AD patients, amnestic bvFTD had greater atrophy of the left fusiform gyrus, temporal poles, right inferior temporal gyrus, insula and cerebellum. Conclusion: We identified that different extrinsic and intrinsic aspects may influence the relationship between episodic memory and its neural correlates including the hippocampus and other structures.